2016
DOI: 10.1007/s11356-016-7618-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and functional properties of protein hydrolysates from fish frame processing waste using plant proteases

Abstract: Enzymatic conversion of fish frame waste of threadfin breams (Nemipterus japonicus) to protein hydrolysate could be a solution for minimizing the pollution issues related to seafood processing operations and a way for the value addition to processing by-products. Protein hydrolysates from fish frame waste (FW) of thread fin breams (N. japonicus) were prepared and evaluated for bioactive properties such as angiotensin-I-converting enzyme (ACE) inhibitory activity and antioxidant and functional properties as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 45 publications
5
42
1
1
Order By: Relevance
“…Furthermore, this previous report also revealed that bromelain exhibited the highest specificity in the generation of ACE-inhibitory peptides from Ulva rigida protein. Other studies on other marine resources, such as different kinds of fish, also showed that bromelain is the most efficient protease tested for the production of protein hydrolysates with higher bioactivities (ACE-inhibitory and/or antioxidant activities) [ 30 , 31 , 32 ]. On the other hand, a molecular weight cut-off (MWCO) dialysis of FSPH was further used as means of enhancing its bioactivities, as well as to provide insights into the molecular weight distribution of the bioactive compounds presented in the hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this previous report also revealed that bromelain exhibited the highest specificity in the generation of ACE-inhibitory peptides from Ulva rigida protein. Other studies on other marine resources, such as different kinds of fish, also showed that bromelain is the most efficient protease tested for the production of protein hydrolysates with higher bioactivities (ACE-inhibitory and/or antioxidant activities) [ 30 , 31 , 32 ]. On the other hand, a molecular weight cut-off (MWCO) dialysis of FSPH was further used as means of enhancing its bioactivities, as well as to provide insights into the molecular weight distribution of the bioactive compounds presented in the hydrolysate.…”
Section: Resultsmentioning
confidence: 99%
“…DPPH and ABTS maximum values varied among 12.4% and 5.1% for Alcalase hydrolysates and 16% and 7.3% for Esperase hydrolysates. These antioxidant activities are lower than those addressed for FPH formulated with different materials and using several enzymes: horse mackerel and subtilisin [ 10 ], red scorpionfish and Flavourzyme [ 32 ], or threadfin bream and Papain [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various types of methods have been used to evaluate the antioxidant activity of fish-derived peptides, including the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging assay, hydroxyl radical scavenging activity, Cu 2+ chelating activity, and Fe 2+ chelating activity [99,100,101,102,103,104,105]. …”
Section: Marine Fish-derived Peptidesmentioning
confidence: 99%